Rabies Postexposure Prophylaxis for Travelers Injured by Nonhuman Primates, Marseille, France, 2001–2014 - Agathe Blaise; Philippe Parola; Philippe Brouqui; Philippe Gautret (Emerging Infectious Diseases, 2015)
Most exposures of residents of Marseille to nonhuman primates occurred among unvaccinated adult travelers to Southeast Asia within the first 10 days of their arrival at 2 major tourist locations in Thailand and 1 in Indonesia. A small proportion of travelers received rabies immunoglobulin in the country of exposure.